PENGARUH HUBUNGAN PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA MANULIFE FINANCIAL INDONESIA). - Denny Asmas (Universitas Batanghari Jambi, 2016)
This research was conducted to find out the influence of managerial performance against budget participation, the influence of participation in managerial performance increase budget through organizational commitment, the influence of organizational commitment on performance of managerial, as well as to know the influence of the participation of the budget and organizational commitment affect managerial performance on PT Asuransi Jiwa Manulife Indonesia or Manulife Financial simultaneouslyIn collecting research data using the intrument research. Intrument research made by the researchers tested the validity and reabilitasnya. Instrument can be kuestionerresearch, observation and interview. The data collected was analyzed further by using statistical analysis of deskriftif and inferensial statistical analysis of Researchers using inferensial because research conducted on random samples taken from a population.The results of hypothesis testing of research it can be concluded that the partial Participation in budget, a budget with participation of organizational commitment as avariable interveningnya, influential organization significant positive Commitment towards managerial performance at manulife financial. Simultaneously, participation and commitment of the Organization's budget a significant positive effect on performance in managerial Manulife Financial with proven significant values 0.000 is uji_F α <.Keywords: participation budget, organizational commitment and managerial performance